Makna Perintah Iqra’ dan Ayat Serupa dalam Tafsir Al-Munir: Studi Tematik Surah Al-‘Alaq, Al-Haqqah, dan Al-Isra - Pauspaus, Bidasari; Iqbal, Ipmawan Muhammad; Rokhani, Siti (The Magister of Islamic Education IAIN Pontianak, 2025)
This study explores the meaning and scope of the command Iqra’ as the first revealed word in the Qur’an, emphasizing its intellectual and spiritual implications. Far beyond its literal meaning